Estudo do mecanismo de ação citotóxica de naftoquinonas sintéticas análogas do lapachol - Costa, Arinice de Menezes (2012)
The lapachol, one naphthoquinone natural, and its derivatives synthetic have demonstrated, in recent years, important actions cytotoxic against several lineages of tumor cells, well as signifier antitumoral activity against some tumors. Thus, the objective this work was to evaluate the mechanisms of action cytotoxic in cells HL-60 of two naphthoquinones synthetic analogous of lapachol (compounds 1 and 2). Initially was investigated at antiproliferative activity these naphthoquinones after a incubation period of 72 hours in leukemic cells (HL-60) and peripheral blood mononucleated cells (PBMC) where was observed that these naphthoquinones were active for these lines with IC50 of 12 µM , 2.3 µM and 4.3 µM for the lapachol, compound 1 and compound 2, respectively in cells HL-60 and 13.7 µM and 34.0 µM for compound 1 and 2 in cells PBMC, respectively. The antiproliferative activity in cells HL-60 after 24 hours incubation was evaluated with and without co-treatment with the antioxidant n-acetylcysteine (NAC). Thus, IC50 without NAC after 24 hours of exposure to lapachol, compound 1 and compound 2 was 42.9 µM, 2.7 µM and 4.3 µM, respectively. Have IC50 with NAC (5 µM) after 24 hours of exposure to lapachol, compound 1 and compound 2 was 180.0 µM, 46.0 µM and 18.0 µM, respectively. Studies done in HL-60 cells indicated that the lapachol and its two analogues induce cell death by apoptosis and necrosis, as shown by morphological changes evaluated through the use of staining May-Grünwald-Giemsa. In trials realisados by flow cytometry was revealed that these compounds promote the generation of reactive oxygen species (ROS) 18.86%, 13.31% and 39.11% respectively for the lapachol (82 µM) and compounds 1 and 2 (3,5 µM) and 40.94% and 60.49% for the compounds 1 and 2 (7.0 µM), respectively. The lapachol (82 µM) and the compounds 1 and 2 (3.5 µM) decreased the number of cells with intact membrane 26.51%, 34.78% and 29.58% respectively and the compounds 1 and 2 (7, 0 µM) decreased 75.3% and 71.1%, respectively. The DNA fragmentation promoted by such compounds was observed starting from 3 hours of exposure being more intense after 24 hours of exposure to tested compounds. The lapachol and the compounds 1 and 2 also promoted the activation of caspases related to intrinsic pathway of cell death. Furthermore, showed induce the synthesis of DNA strands. All cytotoxic effects were abolished when the compounds 1 and 2 were co-incubated with the NAC, showing thus the participation ROS in cytotoxicity these naphthoquinones.